Domino : a manual to use peer group education as a meant to fight racism, xenophobia, anti-semitism, and intolerance - Taylor, Mark, 1973-; Gomes, Rui Machado, 1955-; Brander, Patricia; Angst, Doris; Council of Europe. Directorate of Youth and Sport ([Place of publication not identified] : Council of Europe, Directorate of Youth and Sport, 2004)
The different sections of this publication contain some theoretical background on peer group education as well as different project descriptions, methods, quotes and stories from young people. The references to resources used have been put in brackets and the sources can be found in the bibliography at the end of this publication. This publication is the result of different youth work practices in several European countries, both in the formal and informal educational sector. The editors have drawn from experiences in youth organizations, youth initiatives and schools. The existing diversity in Europe is also reflected in the presentation of different practical approaches.--Publisher's description.
Section 1. Introduction -- How to work with DOmino -- Section 2. What is peer group education? -- Rationale of peer education -- Peer education, peer learning and peer led approaches -- Section 3. Why use peer group education for the campaign "all different : all equal"? -- Section 4. Stories told by young people -- Section 5. Examples of good practice -- Section 6. Step by step -- How to start a peer group education programme -- Step by step checklist -- Section 7. Your project is running : how to coach it? -- 12 points for the supportive and non-authoritarian coach -- Section 8. 9 sessions for training peer coaches -- Section 9. Peer education training days.
Includes bibliographical references (pages 97-99).
Available both in print and online.
Keywords: Multicultural education -- Europe; Discrimination -- Study and teaching -- Activity programs -- Europe; Toleration -- Study and teaching -- Activity programs -- Europe; Peer counseling -- Europe; Youth workers -- Europe; Multicultural education; Peer counseling; Youth workers; Europe